Relationships between results of an internal and external match load determining method in male, singles badminton players - Abdullahi, Y.; Coetzee, B.; van den Berg, L. (The Journal of Strength and Conditioning Research, 2019)
The purpose of study was to determine relationships between results of an internal and external match load determining method. Twenty-one players who participated in selected badminton championships during the 2014/2015 season served as subjects. The heart rate (HR) values and global positioning system (GPS) data of each player were obtained using a fix Polar HR Transmitter Belt and MinimaxX GPS device. Moderate significant Spearman's rank correlations were found between HR and absolute duration (r = 0.43 at a low intensity [LI] and 0.44 at a high intensity [HI]), distance covered (r = 0.42 at a HI), and player load (r = 0.44 at a HI). Results also revealed an opposite trend for external and internal measures of load, as the average relative HR value was found to be the highest for the HI zone (54.1%) compared with the relative measures of external load where average values (1.29-9.89%) were the lowest for the HI zone. In conclusion, our findings show that results of an internal and external badminton match load determining method are more related to each other in the HI zone than other zones and that the strength of relationships depend on the duration of activities that are performed in especially LI and HI zones. Overall, trivial to moderate relationships between results of an internal and external match load determining method in male, singles badminton players reaffirm the conclusions of others that these constructs measure distinctly different demands and should therefore be measured concurrently to fully understand the true requirements of badminton match play.